Extrasynaptic NMDA receptor dependent long-term potentiation of hippocampal CA1 pyramidal neurons - Qian Yang (Nature Portfolio, 2017)
Abstract In the adult mouse hippocampus, NMDA receptors (NMDARs) of CA1 neurons play an important role in the synaptic plasticity. The location of NMDARs can determine their roles in the induction of long-term potentiation (LTP). However, the extrasynaptic NMDARs (ES-NMDARs) dependent LTP haven’t been reported. Here, through the use of a 5-Hz stimulation and MK-801 (an irreversible antagonist of NMDARs) in the CA1 neurons of adult mice hippocampal slices, synaptic NMDARs were selectively inhibited and NMDAR-mediated excitatory postsynaptic currents were not recovered. We found that a robust LTP was induced by 3-train 100-Hz stimulation when the synaptic NMDARs and extrasynaptic NR2B containing NMDARs were blocked, but not in the any of the following conditions: blocking of all NMDARs (synaptic and extrasynaptic), blocking of the synaptic NMDARs, and blocking of the synaptic NMDARs and extrasynaptic NR2A-containing NMDARs. The results indicate that this LTP is ES-NMDARs dependent, and NR2B-containing ES-NMDARs modulates the threshold of LTP induction.